Effectiveness of Virtual Reality on Theory of Mind in Children with Autism Spectrum Disorder - Keshvari Hamid, Davood; Ebrahmipour, Majid; Vakili, Samira (KMAN Counseling & Psychology Nexus, 2025)
The present study was conducted with the aim of examining the effectiveness of virtual reality on theory of mind in children with Autism Spectrum Disorder (ASD). The research design was quasi-experimental with a pretest–posttest structure and a control group. The statistical population consisted of all children with ASD in the city of Arak in 2025. The sample included 30 children aged 7 to 12 years diagnosed with ASD, who were purposively selected through clinical file review and diagnostic confirmation by a specialist in neurodevelopmental disorders or a child psychiatrist. The children were then randomly assigned to two groups of 15: experimental and control. First, theory of mind in both groups was assessed using the Stierman Performance Test (pretest). The experimental group then received a virtual reality intervention for 15 sessions, each lasting 35 minutes, delivered twice per week. After completion of the intervention, theory of mind in both groups was reassessed using the Stierman Performance Test (posttest), followed by a two-month follow-up assessment to evaluate treatment stability. Data were analyzed using repeated-measures analysis of variance with both between-group and within-group factors. The findings indicated a statistically significant difference between the experimental and control groups in theory of mind (p < .05). The results demonstrated that virtual reality is effective in improving theory of mind in children with ASD.